Kinerja Pegawai Pada Bidang Penelitian Dan Pengembangan Di BAPPEDA LITBANG Kabupaten Pasangkayu - Aris Pebriansyah; Syahruddin Hattab; Abdul Rivai (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to describe and analyze employee performance in the Research and Development Division of BAPPEDA Litbang Pasangkayu District. A qualitative approach was utilized to deeply analyze the topic and gain an accurate understanding of the research objectives. The grand theory employed in this research is based on Robbins' theory, focusing on five main aspects: Quality, Quantity, Timeliness, Effectiveness, and Independence. The research findings indicate that employee performance in carrying out tasks and functions in the research and development field at BAPPEDA Pasangkayu District is effective. However, constraints related to the number of employees remain a significant issue affecting performance quantity. Effective time management strategies are required to address excessive workloads, while prudent budget allocation and human resource management are key to achieving research and development objectives. Additionally, findings regarding independence indicators suggest that some employees still tend to delegate their tasks to honorary staff. Therefore, efforts are needed to provide training and capacity building for civil servant employees to enhance their independence in task completion. It is hoped that the implementation of these strategies will optimize employee performance in the research and development field and ensure the success of planned programs